Decoy Oligodeoxynucleotides, Polysaccharides, and Targeted Peptide‐Functionalized Gold Nanorods for the Combined Treatment of Rheumatoid Arthritis. Issue 20 (25th September 2019) - Zhang, Nan; Zhang, Shasha; Xu, Chunyu; Fu, Lingling; Liu, Tuanbing; Zhao, Yongxing
Abstract : Adv. Healthcare Mater . 2018, 7, 1800982 The above article, published online on 04 November 2018 in Wiley Online Library (https://wileyonlinelibrary.com ), has been retracted by agreement between the authors, the journal Editor‐in‐Chief, and Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim. The retraction has been agreed due to errors in data presentation and non‐reproducibility of the results. N. Zhang, S. S. Zhang, C. Y. Xu, L. L. Fu, T. B. Liu, Y. X. Zhao, Adv. Healthcare Mater. 2018, 7, 1800982, DOI:10.1002/adhm.201800982 .